2004
DOI: 10.1128/iai.72.5.2780-2790.2004
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Hematin by a New Class of Glutathione Transferase from the Blood-Feeding Parasitic NematodeHaemonchus contortus

Abstract: The phase II detoxification system glutathione transferase (GST) is associated with the establishment of parasitic nematode infections within the gastrointestinal environment of the mammalian host. We report the functional analysis of a GST from an important worldwide parasitic nematode of small ruminants, Haemonchus contortus. This GST shows limited activity with a range of classical GST substrates but effectively binds hematin. The high-affinity binding site for hematin was not present in the GST showing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 35 publications
6
50
0
Order By: Relevance
“…Sequence comparison with GSTs from other organisms demonstrated that GSTs from hookworms are from a novel family of nematode-specific GSTs designated the nu class (54). The nematode-specific nu-class GSTs are functionally and structurally different from other classes of GSTs and are characterized by a high-affinity binding site for heme and its related products and limited activity with other substrates (59,69). The crystal structures of nu-class GSTs contain long/deep and large clefts FIG.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sequence comparison with GSTs from other organisms demonstrated that GSTs from hookworms are from a novel family of nematode-specific GSTs designated the nu class (54). The nematode-specific nu-class GSTs are functionally and structurally different from other classes of GSTs and are characterized by a high-affinity binding site for heme and its related products and limited activity with other substrates (59,69). The crystal structures of nu-class GSTs contain long/deep and large clefts FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The IC 50 of hematin for rNa-GST-2-conjugating activity was 3-to 5-fold lower than those of the other hookworm GSTs, implying that Na-GST-2 exhibited the highest affinity for heme. The hookworm GSTs' heme-binding K d values were about 10-fold larger than their corresponding IC 50 s, suggesting that quenching of intrinsic fluorescence detects a heme-binding site distinct from the active site, as seen for Hc-GST-1 from Haemonchus contortus (59).…”
Section: Na-gst-3 May Represent Cross-reactivity Of Residual Antibodimentioning
confidence: 99%
See 3 more Smart Citations